A review of the latest progress in superhydrophobic surface technology using copper oxide nanoparticles - Suriani binti Abu Bakar (Tanjung Malim, 2024)
A review of the latest progress in superhydrophobic surface technology using copper oxide nanoparticles by Suriani binti Abu Bakar